The effect of treatment with a non-ionic surfactant vesicular formulation of sodium stibogluconate on host immune responses and serum metabolites in a murine model of Leishmania donovani - Aruleba, Raphael Taiwo; Osero, Bernard Ong’ondo; Loots, Du Toit; Luies, Laneke; Cele, Zama; Opare, Priscilla Abena Ankamaa; van Reenen, Mari; Brombacher, Frank; Carter, Katharine C.; Hurdayal, Ramona (Frontiers in Immunology, 2025)
IntroductionVisceral leishmaniasis (VL), caused by Leishmania donovani, is associated with parasite-induced immunological and physiological changes that ensure the survival of amastigotes within the host. Both the parasite and the host have nutritional requirements, and for auxotrophic Leishmania, dependence on the host to supply specific growth requirements is essential. This highlights an intricate link between host immunity and metabolism during VL. This study explores the interplay between the host metabolome and immune responses pre- and post-infection and treatment, aiming to identify early metabolite markers of therapeutic success against Leishmania.MethodsBALB/c mice infected with L. donovani were divided into cured and non-cured groups based on treatment with a non-ionic surfactant vesicle formulation of sodium stibogluconate (300 mg Sbv/kg, SSG-NIV) or PBS vehicle control. Specific immune responses were determined at day 21 and day 60 post-infection, and serum metabolite levels was measured using untargeted GC×GC-TOFMS metabolomics.Results and discussionsTreatment effectively reduced parasite loads, triggering heightened CD4+ and CD8+ T-cell responses at day 21, with increased IFN-γ, IL-12, and IL-4, and decreased IL-10 and TGF-β. Pre-treatment metabolomics analysis identified changes in glycolysis, fatty acid and amino acid metabolism 1-week PI, suggesting an increased Warburg effect to supplement parasite survival and initiation of immune responses. Valine, lactic acid, and glycerol-1-oleate were identified as markers of early infection. Treatment with SSG-NIV altered metabolism of major macromolecules and the TCA cycle relative to non-cured groups. Additionally, glycine and ribitol show promise as immune correlates for antiparasitic therapies. These findings highlight the diagnostic and prognostic potential of serum-derived metabolites in monitoring host immune responses to VL and treatment.